“Turn-on” mode fluorescence detection of amines based on a cationic covalent organic framework linked with C−C single bond - Feng, Xue-Nan; Liu, Xiao-Yang; Cao, Dong-Xiao; Zhou, Yun-Jie; Cui, Yun-Xi; Kong, De-Ming (Journal of hazardous materials, 2025)
Developing methods to detect amine pollutants at trace levels is urgently needed due to their high toxicity to both human health and environment. Covalent organic frameworks (COFs) have emerged as promising candidates for amine sensing due to their exceptional stability when exposed to corrosive amines. While several COF-based sensors have recently been developed for amine detection, to the best of our knowledge, fluorescent “turn-on” sensors have been limited to imine-linked COFs. However, the relatively low stability of imine linkages may compromise structural integrity in the presence of corrosive amines. Here, for the first time, we constructed a cationic C−C single bond linked COF (CSBL-COF-4) through the reaction between cationic porphyrin TMPyP and terephthaldicarboxaldehyde. The abundant cationic sites distributing throughout the networks not only improved the dispersity of CSBL-COF-4 in aqueous solution but also provided numerous acidic sites to enhance the affinity with alkaline amines via Lewis acid-base interaction. CSBL-COF-4 exhibited an efficient response to amine solutions or vapors and was further utilized to evaluate the freshness of meat samples, highlighting its potential for practical applications. Our result would thus open up a new avenue towards constructing a broader class of COF-based sensors for the fluorescence “turn-on” detection of amines. [Display omitted] •The first report on CSBL-COF as a chemosensor for detection of amines.•High stability makes CSBL-COF-4 suitable for use in corrosive environments.•The “turn-on” mode makes CSBL-COF-4 more convenience for further applications.•The successful use in meat freshness evaluation shows the real-world potential.